Karakterisasi Buah Mangga Berdasarkan Nilai Dielektrik Menggunakan Teknik Double-Ring Resonator - Suthami Ariessaputra; Cahyo Mustiko Muvianto; Kurniawan Yuniarto; Sudi Mariyanto Al Sasongko; Syafaruddin Ch (LPPM Universitas Mataram, 2020)
Mango is one of the agricultural products in West Nusa Tenggara Province. The quality of post-harvest mangoes also needs to be known so that the quality produced can be maintained. Fruit quality in the tropics can be seen from the respiration rate, hardness, weight loss, total soluble content (TSC), discoloration and acid content. In addition, the quality of post-harvest mangoes can also be detected using sensors that emit microwaves with a certain value. This technique is non-destructive so it does not damage the object used. Double-ring resonators are used as sensors to detect the characteristics of mangoes. Vector Network Analyzer (VNA) is used as a tool to produce S11 and S21 skatering values, then the skatering values are processed into dielectric values. The test was carried out on the type of Gincong Gincu Mango which was divided into 4 categories, namely ripe mango on the tree, very ripe, thick and raw. Double ring resonator sensor can detect and distinguish the maturity level of mangoes based on the value of S21 in the frequency range of 0.39 to 0.49 GHz. In that frequency range, the average gain value of ripe on tree is -21.4 dB, over ripe is -22.8 dB, early ripe is -25.4 dB and unrip mango is -33.4 dB. While the characterization of mangoes using impedance values can be seen in the frequency range of 0.41 - 0.47 GHz. The average impedance value of ripe on tree is about 0.073, over ripe is about 0.067, early ripe is about 0.057 and unripe mangos is about 0.032